Experimental investigation on the characteristics of heat exchangers based on organic Rankine cycle system under different operating conditions. (25th March 2021) - Lei, Meng; Ma, Xinling; Lian, Qifei; Meng, Xiangrui; Wu, Tan; Wei, Xinli
Summary: Heat exchangers are crucial equipment, and the research related to organic Rankine cycle system is also of paramount importance. Experiments were carried out in a self‐built test rig with the radial inflow turbine as the expander under three operating conditions. By analyzing UA values, the heat transfer area in different stages of evaporation or condensation was roughly calculated, so as to understand the operation performance of heat exchangers and its influence on system. Experimental results show that the heat transfer area in gas‐phase region accounts for a great proportion of evaporator at the beginning with the rising flow rate of R245fa, and finally insufficient heat transfer area is preferentially provided for the preheating and superheating sections. The turning point occurs when the flow rate of R245fa is 800 kg/h, where the distribution of heat transfer area is relatively balanced with optimum system performance. Excessive heat transfer oil flow rate also results in disequilibrium distribution of heat transfer area in the evaporation process. Meanwhile, the optimal flow rate of heat transfer oil is 4 m 3 /h with maximum thermal efficiencies. Besides, through the comparative analysis of the UA values, the stability of the condenser in the ORC system is better than that of the evaporator under different operating conditions. Highlights: The characteristics of the heat exchangers based on ORC system are investigated. The distribution of heat transfer area in each stage of evaporation is analyzed. The stability of the condenser is better than that of evaporator in experiments. The performance of the system is optimal under suitable operating conditions.